The impact of anthropogenic activities on the physicochemical characteristics of Cheleleka peat, Ethiopia - Haymanot Tesfaye; Bikila Warkineh (Journal of Degraded and Mining Lands Management, 2021)
Cheleleka peatland is located at the eastern side of Lake Hawassa and its biological communities face a variety of anthropogenic factors such as agricultural expansion, water diversion, settlement and subsequent peatland drainage and peat extraction. The decomposing products were influenced by various anthropogenic activities. This study aims to identify the impact of human activities on peat characteristics. The result indicates that the peat soil is acidic having a pH value ranging from 4.1-to-4.7 and containing humic acid due to excessive accumulation of organic matter and nutrients. The maturity level of the peat was almost similar in all study sites, except for the Daka site, and are classified under mostly decomposed. At Wesha, Werka, Wendo, Shalo, Cheffe, and Wendo, sites the maturity of the peat was classified under sapric soil. Exceptionally, at Daka Site, the peat maturity level was hemic. The percentage of sand, clay, and silt of the peatland range 40-50% clay, 30-40% silt and 10-20% sandy. The mean organic carbon content of Cheleleka peatland ranged from 4.48 to 38.65% and positively correlated with the thickness of the peat and negatively correlated with the ash content of the peat. The main effects of unsustainable landuse practice on peatland are peat reduction/complete loss, reduce water and nutrient retention capacity due to drainage and compaction of peat due to overgrazing. Changes in drainage, vegetation cover, and extraction of peat had resulted in differing outcomes from decomposition processes, and the properties of peats on the disturbed sites had changed.